ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA PADA POKOK BAHASAN STATISTIKA DI KELAS XI SMA N 08 TANJUNG JABUNG TIMUR TAHUN AJARAN 2015/2016 - Ayu Yarmayani; Dina Aulia; Silvia Fitriani (PHI: Jurnal Pendidikan Matematika, 2017)
The purpose of this study is to determine: (1) Types of mistakes made by students in solving statistical problems. (2) Factors that cause students to make mistakes. The type of research used is qualitative research, which uses descriptive research methodology. Research subjects are all students of class XI IPA SMA Negeri 08 Tanjung Jabung East with the number of students 61 people. From all students of class XI IPA will be selected 4 people as informant. The data collected in this research are observation, diagnostic test of satistical description, and interview to students who made the most mistake and varied. The errors are done students in solving math problems on the subject statistics are analyzed by type of concept error, data use error, engineering error, language interpretation error, conclusion withdrawal error. The results showed that students make mistakes in solving statistical problems. The types of errors are concept errors, data use errors, technical errors and errors of inference. And the biggest mistake is the concept mistake. The factors that cause these mistakes are the students are less mastering the material, students are less thorough, students in haste and students dont understand the steps of completion.Keywords: Error Analysis, Problem Solving, Statistics